Diffusion source, preparation method thereof and processing method of neodymium-iron-boron magnet

By attaching rare earth element-containing particles and non-rare earth metal oxides to aluminum or aluminum alloy foils, forming a diffusion source and performing heat treatment, the problem of degradation of NdFeB magnets at high temperatures is solved, and the coercive force and magnetic energy of the magnet are improved The amount of rare earth elements is reduced.

CN119252637APending Publication Date: 2025-01-03BAOTOU RESEARCH INSTITUTE OF RARE EARTHS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411376134.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing neodymium iron boron magnets have reduced coercive force, magnetic energy accumulation and residual magnetism under high temperature conditions, and the grain boundary diffusion precursor has low reactivity and is difficult to diffuse effectively, resulting in poor magnet performance.

Method used

Aluminum or aluminum alloy foil is used as diffusion sources, and rare earth element particles and non-rare earth metal oxides are attached to the surface, and a diffusion source is formed through heat treatment, which increases the coercivity of the magnet and reduces the amount of rare earth elements.

Benefits of technology

It effectively improves the coercive force and magnetic energy product of neodymium iron boron magnets, reduces the impact on residual magnetism and squareness, and improves the utilization rate of rare earth elements and the binding force of diffusion sources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005068717940000131
    Figure BDA0005068717940000131
  • Figure BDA0005068717940000141
    Figure BDA0005068717940000141
  • Figure BDA0005068717940000142
    Figure BDA0005068717940000142
Patent Text Reader

Abstract

The invention discloses a diffusion source, a preparation method of the diffusion source and a processing method of a neodymium-iron-boron magnet. The diffusion source comprises aluminum or aluminum alloy foil, wherein rare earth element-containing particles, non-rare earth metal oxide and non-rare earth metal are attached to the upper surface and the lower surface of the aluminum or aluminum alloy foil respectively; the rare earth elements in the rare earth element-containing particles are selected from one or more of terbium, dysprosium, praseodymium and neodymium; the rare earth element-containing particles are selected from one or more of rare earth hydride particles, rare earth fluoride particles and rare earth metal particles; the non-rare earth metal oxide is selected from one or more of aluminum oxide and magnesium oxide; the non-rare earth elements in the non-rare earth metals are selected from one or more of copper, aluminum, magnesium, iron, zirconium, niobium and gallium. The diffusion source can reduce the use amount of rare earth elements and effectively improve the coercive force of the neodymium-iron-boron magnet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a diffusion source and a preparation method thereof and a method for processing a neodymium iron boron magnet. Background Art

[0002] Sintered NdFeB magnets are widely used in high-end fields such as new energy, information communication and intelligent manufacturing due to their excellent magnetic properties. However, with the increase of working temperature, the coercive force, magnetic energy product and remanence of the magnets will be greatly reduced, which makes the magnets unable to meet the use requirements under high temperature conditions. Grain boundary diffusion adds heavy rare earth elements to replace Nd in the main phase, which improves the coercive force of the magnet. Suitable diffusion precursors during grain boundary diffusion can improve the grain boundary diffusion depth and element distribution uniformity of Nd-Fe-B magnets, and effectively improve the squareness and coercive force of the magnet. At present, most of the grain boundary diffusion precursors are heavy rare earth compounds, such as oxides, fluorides and hydrides. These precursors have problems such as low reactivity and high melting point. They are still solid at the diffusion temperature, making it difficult for the grain boundary diffusion precursors to enter the interior of the magnet and accumulate on the surface of the magnet. Moreover, during diffusion, O 2- 、F - The negative ions will enter the magnet together.

[0003] CN118609942A discloses a magnetic diffusion source film, comprising an upper substrate film, a diffusion source and a lower substrate film. The diffusion source comprises a general formula of RE a W b alloy and adhesive. RE is at least one of Dy, Tb, Pr, Nd, La, Ce, Y, Gd, and Ho; W is at least one of Cu, Al, Ga, In, Sn, Fe, Co, Ni, Ti, Zr, and Mg. The upper substrate film and the lower substrate film are made of one or more of polyvinyl alcohol, polyurethane, polycarbonate, and polyethylene terephthalate, respectively. The diffusion source uses high molecular organic matter as the upper substrate film and the lower substrate film, resulting in excessive C, O and other elements being introduced into the magnet.

[0004] CN114717469A discloses a diffusion source for R-Fe-B rare earth permanent magnet materials, comprising heavy rare earth metal elements and auxiliary metal elements, wherein the heavy rare earth elements are one or more of Dy, Tb and Ho, and the auxiliary metal elements are one or more of Cu, Al and Ga, and the content of the auxiliary metal elements accounts for 1-10% of the total mass. The diffusion source has a high content of heavy rare earth elements and a high cost. Summary of the invention

[0005] One object of the present invention is to provide a diffusion source for NdFeB magnets, which can reduce the amount of rare earth elements, effectively improve the coercive force of NdFeB magnets, and have little effect on the remanence, maximum magnetic energy product and squareness of the magnets. Furthermore, the diffusion source of the present invention can selectively diffuse and modify NdFeB magnets. Another object of the present invention is to provide a method for preparing a diffusion source for NdFeB magnets, which has a simple process and can be carried out continuously. Furthermore, the preparation method can improve the bonding force between the attachment and the metal foil, the tight bonding between the attachments, and the solid content. Yet another object of the present invention is to provide a method for treating NdFeB magnets, which can reduce the amount of rare earth elements, improve the coercive force of NdFeB magnets, and have little effect on the remanence, maximum magnetic energy product and squareness of the magnets.

[0006] The above object is achieved through the following scheme.

[0007] In one aspect, the present invention provides a diffusion source for NdFeB magnets, comprising aluminum or aluminum alloy foil, wherein rare earth element-containing particles, non-rare earth metal oxides, and non-rare earth metals are attached to the upper and lower surfaces of the aluminum or aluminum alloy foil, respectively;

[0008] The rare earth element in the rare earth element-containing particles is selected from one or more of terbium, dysprosium, praseodymium, and neodymium; the rare earth element-containing particles are selected from one or more of rare earth hydride particles, rare earth fluoride particles, and rare earth metal particles; the rare earth metal particles are selected from one or more of rare earth single substance particles, alloy particles formed between rare earth elements, and alloy particles formed between rare earth elements and non-rare earth elements;

[0009] The non-rare earth metal oxide is selected from one or more of aluminum oxide and magnesium oxide;

[0010] The non-rare earth metal element in the non-rare earth metal is selected from one or more of copper, aluminum, magnesium, iron, zirconium, niobium and gallium.

[0011] The diffusion source according to the present invention preferably further comprises a copper or alloy foil, wherein the copper or alloy foil covers the rare earth element-containing particles, non-rare earth metal oxides and non-rare earth metals attached to the upper and lower surfaces of the aluminum or aluminum alloy foil, and the thickness of the copper or alloy foil is 1 to 50 μm;

[0012] The aluminum or aluminum alloy foil is selected from one or more of a non-porous foil, a foil with a mesh structure, and a foam metal foil.

[0013] According to the diffusion source of the present invention, preferably, the D 50≤10μm; the rare earth element-containing particles contain one or more of terbium or dysprosium; the rare earth element-containing particles contain non-rare earth metal elements, and the non-rare earth metal elements contained in the rare earth element-containing particles are selected from one or more of copper or aluminum; the rare earth element content in the rare earth element-containing particles is ≥25wt%;

[0014] The particle size of the non-rare earth metal oxide is 200-450 mesh;

[0015] The non-rare earth metal contains copper; based on the mass of the non-rare earth metal, the content of copper is ≥70wt%.

[0016] According to the diffusion source of the present invention, preferably, the content of the rare earth element particles is 10-30 parts by weight, the content of the non-rare earth metal oxide is 0.5-3 parts by weight, and the content of the non-rare earth metal is 0.5-3 parts by weight.

[0017] According to the diffusion source of the present invention, preferably, L0 is 1-100 μm, and L1-L0 is 50-150 μm; wherein L0 represents the thickness of the aluminum or aluminum alloy foil, and L1 represents the thickness of the diffusion source.

[0018] On the other hand, the present invention provides a method for preparing the above-mentioned diffusion source for NdFeB magnets, comprising the following steps:

[0019] Applying a slurry containing rare earth element particles, non-rare earth metal oxides, non-rare earth metals, a binder and a solvent to the upper and lower surfaces of an aluminum or aluminum alloy foil;

[0020] and optionally, covering copper or its alloy foil on the slurry attached to the upper and lower surfaces of the aluminum or aluminum alloy foil,

[0021] Thus, a prefabricated object is obtained;

[0022] The preform is heat treated under the condition of applying pressure to the upper surface and the lower surface of the preform to obtain a diffusion source.

[0023] According to the preparation method of the present invention, preferably, the thickness of the preform is 80-250 μm; and the thickness of the diffusion source is 60%-90% of the thickness of the preform.

[0024] According to the preparation method of the present invention, preferably, a pressure of 5 to 80 MPa is applied to the upper and lower surfaces of the preform and the preform is cured at a temperature of 80 to 160° C. for 1 to 7 minutes; and then the cured preform is degreased at a temperature of 230 to 290° C. for 15 to 90 minutes.

[0025] On the other hand, the present invention provides a method for processing NdFeB magnets, comprising the following steps: subjecting the NdFeB magnets, at least a portion of whose surfaces are covered with the diffusion source, to heating, diffusion and aging treatment to obtain treated magnets.

[0026] According to the treatment method of the present invention, preferably, the heating diffusion is at least two-stage; the primary diffusion temperature is 600-900°C, the primary diffusion time is 60-240min, the secondary diffusion temperature is 850-960°C, and the secondary diffusion time is 200-500min;

[0027] Optionally, pre-diffusion is performed before the primary diffusion, the pre-diffusion temperature is 350-480° C., and the pre-diffusion time is 10-60 min.

[0028] The diffusion source of the present invention can reduce the amount of rare earth elements used, effectively improve the coercive force of the NdFeB magnet, and have little effect on the remanence, maximum magnetic energy product and squareness of the magnet. The diffusion source of the present invention is easy to achieve gravity-assisted diffusion and magnet selective diffusion, and improves the utilization rate of rare earth elements. The preparation method of the present invention is simple, and the bonding strength between the metal foil and the attachment in the obtained diffusion source is high, the attachments are tightly bonded, and the solid content is high. The processing method of the NdFeB magnet of the present invention can reduce the amount of rare earth elements used, effectively improve the coercive force of the NdFeB magnet, and have little effect on the remanence, maximum magnetic energy product and squareness of the magnet. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited thereto.

[0030] <Diffusion Source for NdFeB Magnets>

[0031] The diffusion source for NdFeB magnets of the present invention comprises aluminum or aluminum alloy foil, and the upper surface and lower surface of the aluminum or aluminum alloy foil are respectively attached with rare earth element particles, non-rare earth metal oxides and non-rare earth metals. The rare earth element particles, non-rare earth metal oxides and non-rare earth metals are collectively referred to as "attachments". In some embodiments, the diffusion source also includes copper or its alloy foil. The copper or its alloy foil is covered on the attachments attached to the upper surface and lower surface of the aluminum or aluminum alloy foil.

[0032] The aluminum or aluminum alloy foil is preferably an aluminum foil. The aluminum or aluminum alloy foil is selected from one or more of a non-porous foil, a foil with a mesh structure, and a foam metal foil. Preferably, the aluminum or aluminum alloy foil is a non-porous foil.

[0033] The thickness of the aluminum or aluminum alloy foil may be represented by L0. L0 is 1 to 100 μm, preferably 3 to 40 μm. In some embodiments, L0 is 5 to 30 μm.

[0034] The rare earth element in the rare earth element-containing particles is selected from one or more of terbium, dysprosium, praseodymium and neodymium. Preferably, the rare earth element-containing particles contain one or more of terbium and dysprosium.

[0035] The rare earth element-containing particles may be selected from one or more of rare earth hydride particles, rare earth fluoride particles, and rare earth metal particles. Preferably, the rare earth element-containing particles are selected from one or more of rare earth hydride particles and rare earth metal particles.

[0036] The rare earth hydride particles may be selected from one or more of terbium hydride, dysprosium hydride, praseodymium hydride, and neodymium hydride. Preferably, the rare earth hydride particles are selected from one or more of terbium hydride and dysprosium hydride.

[0037] The rare earth fluoride particles may be selected from one or more of terbium fluoride, dysprosium fluoride, praseodymium fluoride and neodymium fluoride. Preferably, the rare earth fluoride particles are selected from one or more of terbium fluoride and dysprosium fluoride.

[0038] The rare earth metal particles can be rare earth single substance particles, alloy particles formed between rare earth elements, and alloy particles formed between rare earth elements and non-rare earth elements. The alloy can be a binary alloy or a ternary alloy. The non-rare earth element in the rare earth metal particles can be selected from one or more of copper and aluminum.

[0039] The content of rare earth elements in the rare earth metal particles is ≥ 25 wt %; preferably, the content of rare earth elements is 30-95 wt %. In some embodiments, the content of rare earth elements in the rare earth metal particles is 35-50 wt %. In other embodiments, the content of rare earth elements in the rare earth metal particles is 80-90 wt %.

[0040] The content of copper in the rare earth metal particles may be 20 to 65 wt %, preferably 30 to 50 wt %.

[0041] The content of aluminum in the rare earth metal particles may be 5 to 25 wt %; preferably 10 to 20 wt %.

[0042] In certain embodiments, the rare earth metal particles are terbium aluminum copper alloy particles. In other embodiments, the rare earth metal particles are praseodymium terbium aluminum alloy particles.

[0043] D containing rare earth element particles 50 ≤10μm; preferably, D 50 is 0.5 to 8 μm; more preferably, D 50 1~3μm.

[0044] The content of the rare earth element-containing particles may be 10 to 30 parts by weight, preferably 15 to 25 parts by weight. In certain embodiments, the content of the rare earth element-containing particles is 16 to 18 parts by weight.

[0045] The non-rare earth metal oxide is selected from one or more of aluminum oxide and magnesium oxide. Preferably, the non-rare earth metal oxide is aluminum oxide.

[0046] The non-rare earth metal oxide can be used in the form of powder. The particle size of the non-rare earth metal oxide can be 200-450 meshes, preferably 250-350 meshes.

[0047] The amount of the non-rare earth metal oxide used may be 0.5 to 3 parts by weight, preferably 0.8 to 2 parts by weight, and more preferably 1 to 1.5 parts by weight.

[0048] The non-rare earth metal may be a non-rare earth metal element or a non-rare earth metal alloy. The non-rare earth metal element is selected from one or more of copper, aluminum, magnesium, iron, zirconium, niobium, and gallium. Preferably, the non-rare earth metal element includes copper. More preferably, the non-rare earth metal is selected from one of copper, copper-gallium alloy, copper-aluminum alloy, and copper-magnesium alloy.

[0049] In the non-rare earth metal, the content of copper is ≥ 70 wt %. In certain embodiments, the content of copper is 75-90 wt %; preferably, the content of copper is 80-85 wt %.

[0050] In the non-rare earth metal, the content of other metal elements except copper may be 10-30 wt %. In some embodiments, the content of other metal elements is 15-18 wt %. In other embodiments, the content of other metal elements is 20-22 wt %.

[0051] Non-rare earth metals can be used in powder form. 50 It can be ≤20μm; preferably, D 50 1 to 15 μm; more preferably, D 50 4~6μm.

[0052] The content of the non-rare earth metal may be 0.5 to 3 parts by weight, preferably 0.8 to 2 parts by weight, and more preferably 1 to 1.5 parts by weight.

[0053] The copper or alloy foil thereof is preferably a copper foil.

[0054] The thickness of the copper or alloy foil may be 1 to 50 μm, preferably 2 to 30 μm, and more preferably 4 to 10 μm.

[0055] L1 may be 60 to 160 μm, preferably 70 to 140 μm, and more preferably 80 to 130 μm. L1 is the thickness of the diffusion source.

[0056] L1-L0 may be 50 to 150 μm, preferably 60 to 130 μm, and more preferably 70 to 120 μm.

[0057] The diffusion source is easy to diffuse on the surface of the NdFeB magnet to form a uniform diffusion layer and enter the interior of the NdFeB magnet. The diffusion source can effectively improve the coercive force of the magnet while reducing the amount of rare earth elements, and has little effect on the remanence, maximum magnetic energy product and squareness of the magnet.

[0058] <Method for preparing diffusion source>

[0059] The method for preparing a diffusion source of the present invention comprises the following steps: (A) a loading step; and (B) a heat treatment step.

[0060] Load Steps

[0061] A slurry containing rare earth element particles, non-rare earth metal oxides, non-rare earth metals, a binder and a solvent is applied to the upper and lower surfaces of aluminum or aluminum alloy foil to obtain a preform. In some embodiments, copper or its alloy foil is also covered on the slurry attached to the upper and lower surfaces of the aluminum or aluminum alloy foil to obtain a preform. This can prevent the slurry from adhering to the pressure device during the subsequent pressurized heat treatment, affecting the integrity and uniformity of the diffusion source and affecting the use effect of the diffusion source; in addition, it can also improve the elemental composition of the diffusion source and improve the modification performance of the diffusion source on the magnet.

[0062] The selection and dosage of the rare earth element-containing particles, non-rare earth metal oxides, and non-rare earth metals are as described above and will not be repeated here.

[0063] The binder may be a polymer binder. The polymer binder may be selected from one or more of a thermosetting resin, a thermoplastic resin, a synthetic rubber, polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), polyimide (PI), and polyvinyl pyrrolidone (PVP). Examples of thermosetting resins include, but are not limited to, epoxy resins, phenolic resins, urea-formaldehyde resins, polyurethanes, and the like. Examples of thermoplastic resins include, but are not limited to, polyvinyl acetal, perchlorethylene, and the like. Examples of synthetic rubbers include, but are not limited to, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, and the like).

[0064] The amount of the binder may be 1 to 3 parts by weight, preferably 1.5 to 2.5 parts by weight.

[0065] The solvent can be selected from one or more of p-methoxybenzyl alcohol, diethylene glycol butyl ether acetate, ethylene glycol diacetate, ethylene glycol ethyl ether acetate, tributyl citrate, α-terpineol, ethanol, acetone, petroleum ether, and isopropanol.

[0066] The solvent may be 10 to 30 parts by weight; preferably 15 to 25 parts by weight.

[0067] The thickness of the preform may be 80 to 250 μm, preferably 100 to 200 μm. In certain embodiments, the thickness of the preform is 120 to 190 μm.

[0068] The aluminum or aluminum alloy foil may be treated before being coated with the slurry. Specifically, the aluminum or aluminum alloy foil is subjected to ultrasonic treatment to remove pollutants on the surface of the aluminum or aluminum alloy foil. The ultrasonic treatment may be performed in the presence of a small molecule monohydric alcohol. Examples of small molecule monohydric alcohols include, but are not limited to, methanol, ethanol, propanol, and isopropanol.

[0069] Heat treatment steps

[0070] Under the condition of applying pressure to the upper and lower surfaces of the preform, the preform is heat treated to obtain a diffusion source. A certain pressure is applied to the upper and lower surfaces of the preform, which can improve the tightness of the attachment (containing rare earth element particles, non-rare earth metal oxides, non-rare earth metals) and reduce the porosity.

[0071] In some embodiments, pressure is applied to the upper and lower surfaces of the preform and the preform is cured under certain temperature conditions; and then the cured preform is degreased. Preferably, a certain pressure is applied to the upper and lower surfaces of the cured preform during the degreasing process.

[0072] The pressure applied to the upper and lower surfaces of the preform may be 5 to 80 MPa, preferably 10 to 50 MPa, and more preferably 20 to 30 MPa. A roller press may be used to apply pressure to the upper and lower surfaces of the preform. This can improve the tightness of contact between the various parts of the diffusion source during the curing process and improve the diffusion effect of the diffusion source.

[0073] The curing temperature may be 80-160° C., preferably 100-140° C., and more preferably 120-130° C. Preferably, infrared heating is used to achieve the curing temperature.

[0074] The curing time may be 1 to 7 minutes, preferably 2 to 5 minutes, and more preferably 3 to 4 minutes.

[0075] The degreasing temperature can be 180-320°C; preferably 200-280°C; more preferably 220-260°C. Preferably, the above degreasing temperature is reached by infrared heating. The degreasing time can be 15-90 minutes; preferably 30-70 minutes; more preferably 40-60 minutes. In this way, some non-metallic elements introduced by the solvent and / or binder can be removed, such as carbon and other elements. The present invention finds that if some non-metallic elements introduced by the solvent and / or binder exist too much in the diffusion source, it will affect the performance of the magnet after diffusion; if these non-metallic elements are retained too little, it will affect the activity of the diffusion source and be unfavorable for diffusion.

[0076] The pressure applied to the upper and lower surfaces of the solidified preform can be 1-50 MPa, preferably 5-20 MPa, and more preferably 6-10 MPa. A roller press can be used to apply pressure to the upper and lower surfaces of the solidified preform. This can improve the tightness of contact between the various parts of the diffusion source during the solidification process and improve the diffusion effect of the diffusion source.

[0077] The preparation method is simple and easy to operate, uses less organic compounds, and the obtained diffusion source has a higher solid content. The attachments are tightly bonded to each other, the bonding strength between the attachments and the metal foil is high, and the attachments are evenly dispersed.

[0078] <Processing Method of NdFeB Magnets>

[0079] The method for treating NdFeB magnets of the present invention comprises the following steps: heating and diffusing the NdFeB magnets at least a portion of which is covered with the diffusion source to obtain diffused magnets. The diffusion source is specifically described above and will not be described in detail here.

[0080] The diffusion source may be covered on the upper surface of the NdFeB magnet, may be covered on the lower surface of the NdFeB magnet, or may be covered on both the upper surface and the lower surface of the NdFeB magnet.

[0081] The surface of the NdFeB magnet may be covered with a single layer of diffusion source or multiple layers of diffusion source, and the multiple layers of diffusion source may be the same or different.

[0082] NdFeB magnets may contain neodymium, praseodymium, cobalt, copper, aluminum, zirconium, titanium, gallium, boron and iron. In certain embodiments, they may also contain dysprosium.

[0083] The content of neodymium may be 15 to 25 parts by weight, preferably 18 to 23 parts by weight.

[0084] The content of praseodymium may be 3 to 10 parts by weight, preferably 5 to 8 parts by weight.

[0085] The content of dysprosium may be 1 to 8 parts by weight, preferably 3 to 6 parts by weight.

[0086] The content of cobalt may be 0.2 to 5 parts by weight, preferably 0.3 to 2.8 parts by weight.

[0087] The content of copper may be 0.1 to 0.8 parts by weight, preferably 0.2 to 0.5 parts by weight.

[0088] The content of aluminum may be 0.05 to 1.2 parts by weight, preferably 0.08 to 1 part by weight.

[0089] The content of zirconium may be 0.05 to 0.8 parts by weight, preferably 0.1 to 0.5 parts by weight.

[0090] The content of titanium may be 0.05 to 0.8 parts by weight, preferably 0.1 to 0.5 parts by weight.

[0091] The gallium content may be 0.05 to 0.5 parts by weight, preferably 0.1 to 0.3 parts by weight.

[0092] The boron content may be 0.7 to 0.98 parts by weight, preferably 0.85 to 0.95 parts by weight.

[0093] The iron content may be 65 to 68 parts by weight, preferably 66 to 67.5 parts by weight.

[0094] The oxygen content in the NdFeB magnet may be 400 to 800 ppm, preferably 500 to 700 ppm.

[0095] The NdFeB magnet may be a sintered NdFeB magnet.

[0096] The NdFeB magnet can be cylindrical, cube, cuboid, or irregular in shape. The thickness of the NdFeB magnet can be 1 to 25 mm, preferably 5 to 15 mm. The diameter of the NdFeB magnet can be 3 to 20 mm, preferably 5 to 15 mm.

[0097] The heating diffusion can be carried out under the condition of pressure <10Pa; preferably, under the condition of pressure <5Pa; more preferably, under the condition of pressure 10 -3 ~10 -4 Pa.

[0098] Diffusion can be performed in multiple stages. In certain embodiments, two-stage diffusion is performed.

[0099] The primary diffusion temperature may be 600 to 900°C, preferably 650 to 850°C. In some embodiments, the primary diffusion temperature is 700 to 800°C. The primary diffusion time may be 60 to 240 min, preferably 90 to 200 min. In some embodiments, the primary diffusion time is 120 to 150 min. The heating rate to the primary diffusion temperature may be 1 to 20°C / min, preferably 5 to 12°C / min.

[0100] The secondary diffusion temperature may be 850-960°C, preferably 880-920°C. In some embodiments, the secondary diffusion temperature is 890-900°C. The secondary diffusion temperature is greater than the primary diffusion temperature. The secondary diffusion time may be 200-500 min, preferably 240-480 min. In some embodiments, the secondary diffusion time is 300-400 min.

[0101] In some embodiments, pre-diffusion is performed before primary diffusion. The pre-diffusion temperature may be 250-500°C, preferably 300-400°C, and more preferably 320-380°C. The pre-diffusion time may be 20-120 min, preferably 40-100 min, and more preferably 60-80 min. The heating rate to the pre-diffusion temperature may be 1-15°C / min, and preferably 3-8°C / min.

[0102] Heating diffusion can be carried out in a vacuum heat treatment furnace.

[0103] The magnet obtained by the diffusion treatment can be cooled to room temperature (20 to 35° C.) to obtain a diffused magnet.

[0104] In some embodiments, the method further comprises the step of subjecting the diffused magnet to an aging treatment to obtain a treated magnet.

[0105] The aging treatment may be performed under the condition of pressure <100 Pa; preferably, pressure <50 Pa; more preferably, pressure <10 Pa.

[0106] The aging treatment temperature may be 400 to 600°C, preferably 450 to 570°C, and more preferably 500 to 560°C. The aging treatment time may be 60 to 300 min, preferably 100 to 250 min. In certain embodiments, the aging treatment time is 150 to 200 min. The heating rate to the aging treatment temperature may be 1 to 15°C / min, preferably 3 to 10°C / min.

[0107] Aging treatment can be carried out in a vacuum heat treatment furnace.

[0108] Here is the test method:

[0109] Magnetic properties: The test was conducted using a NIM-10000HC permanent magnet tester. The magnet was processed into a cylinder with a diameter of 10 mm and a height of 10 mm by wire cutting. The test temperature was 20°C. The test standard was GB / T 3217:2013.

[0110] Here are the raw materials:

[0111] The contents of various elements in the terbium aluminum-copper alloy are: 38.5wt% terbium, 15.4wt% aluminum, and 46.1wt% copper.

[0112] The contents of each element in the praseodymium-terbium-aluminum alloy are: praseodymium 62.3wt%, terbium 24.8wt%, and aluminum 12.9wt%.

[0113] The contents of various elements in the copper-gallium alloy powder are: copper 78.2wt%, gallium 21.8wt%.

[0114] The content of each element in the copper-aluminum alloy powder is: copper 82.5wt%, aluminum 17.5wt%.

[0115] The contents of various elements in the copper-magnesium alloy powder are: 83.2wt% copper and 16.8wt% magnesium.

[0116] Embodiments 1 to 5

[0117] The dense non-porous aluminum foil is ultrasonically treated in anhydrous ethanol to obtain the treated aluminum foil.

[0118] The rare earth element particles, alumina, non-rare earth metals, a binder and a solvent are mixed and then stirred thoroughly to obtain a slurry.

[0119] The slurry is uniformly coated on the upper and lower surfaces of the treated aluminum foil, and then in certain embodiments, a dense, non-porous copper foil is covered on the slurry coated on the upper and lower surfaces of the aluminum foil to obtain a preform.

[0120] Under the condition of applying 25MP pressure on the upper and lower surfaces of the preform, the preform is infrared heated and cured at 120°C for 3 minutes. A pressure of 6MPa is applied to the upper and lower surfaces of the cured preform, and the temperature is raised to 260°C for degreasing for 45 minutes to obtain a diffusion source with a smooth surface and close contact of rare earth element particles inside. Pressure is applied to the upper and lower surfaces of the preform by a roller press.

[0121] The raw materials and parameters are shown in Table 1.

[0122] Table 1

[0123]

[0124]

[0125] Embodiments 6 to 10

[0126] The diffusion source is covered on the upper surface of the sintered NdFeB magnet and then placed in a vacuum heat treatment furnace. The composition of the sintered NdFeB magnet and the selection of the diffusion source are shown in Table 2. The diameter of the sintered NdFeB magnet is 10 mm and the thickness is 5 mm.

[0127] Table 2

[0128]

[0129] The pressure in the vacuum heat treatment furnace is 10 -3 ~10 -4 Pa, multi-stage diffusion was carried out and then cooled to 26°C to obtain a diffused magnet.

[0130] The diffused magnet is placed in a vacuum heat treatment furnace, under the condition of pressure <10Pa, and heated from the initial temperature (26°C) to T1, kept at T1 for t1, and then rapidly cooled to 26°C to obtain the treated magnet. When the temperature rises to T1, the pressure in the furnace chamber is ≤10 -3 .

[0131] The specific parameters of diffusion and aging treatment are shown in Table 3. The magnetic properties of NdFeB magnets and the treated magnets are shown in Table 4.

[0132] Table 3

[0133]

[0134] Note: “—” for pre-diffusion temperature and pre-diffusion time means no pre-diffusion is performed and primary diffusion is performed directly.

[0135] Table 4

[0136]

[0137] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A diffusion source for NdFeB magnets, characterized in that: The diffusion source comprises aluminum or aluminum alloy foil, and the upper surface and lower surface of the aluminum or aluminum alloy foil are respectively attached with rare earth element particles, non-rare earth metal oxides and non-rare earth metals; The rare earth element in the rare earth element-containing particles is selected from one or more of terbium, dysprosium, praseodymium, and neodymium; the rare earth element-containing particles are selected from one or more of rare earth hydride particles, rare earth fluoride particles, and rare earth metal particles; the rare earth metal particles are selected from one or more of rare earth single substance particles, alloy particles formed between rare earth elements, and alloy particles formed between rare earth elements and non-rare earth elements; The non-rare earth metal oxide is selected from one or more of aluminum oxide and magnesium oxide; The non-rare earth metal element in the non-rare earth metal is selected from one or more of copper, aluminum, magnesium, iron, zirconium, niobium and gallium.

2. The diffusion source according to claim 1, characterized in that: It also includes copper or its alloy foil, which covers the rare earth element-containing particles, non-rare earth metal oxides and non-rare earth metals attached to the upper and lower surfaces of the aluminum or aluminum alloy foil, and the thickness of the copper or its alloy foil is 1 to 50 μm; The aluminum or aluminum alloy foil is selected from one or more of a non-porous foil, a foil with a mesh structure, and a foam metal foil.

3. The diffusion source according to claim 1, characterized in that: The rare earth element-containing particles D 50 ≤10μm; the rare earth element-containing particles contain one or more of terbium or dysprosium; the rare earth element-containing particles contain non-rare earth metal elements, and the non-rare earth metal elements contained in the rare earth element-containing particles are selected from one or more of copper or aluminum; the rare earth element content in the rare earth element-containing particles is ≥25wt%; The particle size of the non-rare earth metal oxide is 200-450 mesh; The non-rare earth metal contains copper; based on the mass of the non-rare earth metal, the content of copper is ≥70wt%.

4. The diffusion source according to claim 1, characterized in that: The content of the rare earth element particles is 10 to 30 parts by weight, the content of the non-rare earth metal oxide is 0.5 to 3 parts by weight, and the content of the non-rare earth metal is 0.5 to 3 parts by weight.

5. The diffusion source according to claim 1, characterized in that: L0 is 1 to 100 μm, and L1-L0 is 50 to 150 μm; wherein L0 represents the thickness of the aluminum or aluminum alloy foil, and L1 represents the thickness of the diffusion source.

6. The method for preparing a diffusion source according to any one of claims 1 to 5, characterized in that: The steps include: Applying a slurry containing rare earth element particles, non-rare earth metal oxides, non-rare earth metals, a binder and a solvent to the upper and lower surfaces of an aluminum or aluminum alloy foil; and optionally, covering copper or its alloy foil on the slurry attached to the upper and lower surfaces of the aluminum or aluminum alloy foil, Thus, a prefabricated object is obtained; The preform is heat treated under the condition of applying pressure to the upper surface and the lower surface of the preform to obtain a diffusion source.

7. The preparation method according to claim 6, characterized in that: The thickness of the preform is 80-250 μm; the thickness of the diffusion source is 60%-90% of the thickness of the preform.

8. The preparation method according to claim 6, characterized in that: The preform is cured for 1 to 7 minutes under the condition of applying a pressure of 5 to 80 MPa to the upper and lower surfaces of the preform at a temperature of 80 to 160° C.; and then the cured preform is degreased for 15 to 90 minutes at a temperature of 230 to 290° C.

9. A method for processing a neodymium iron boron magnet, characterized in that: The steps include: A NdFeB magnet at least a portion of which is covered with the diffusion source according to any one of claims 1 to 5 is subjected to heating diffusion and aging treatment to obtain a treated magnet.

10. The processing method according to claim 9, characterized in that: The heating diffusion is at least two-stage; the first-stage diffusion temperature is 600-900°C, the first-stage diffusion time is 60-240 minutes, the second-stage diffusion temperature is 850-960°C, and the second-stage diffusion time is 200-500 minutes; Optionally, pre-diffusion is performed before the primary diffusion, the pre-diffusion temperature is 350-480° C., and the pre-diffusion time is 10-60 min.

Citation Information

Cited By

  • Mixed grain boundary diffusion source for sintering NdFeB magnet and preparation method and application of mixed grain boundary diffusion source

    CN121483855A